Youth co-authorship as public engagement with geoengineering. Issue 1 (2nd January 2022) - Dunlop, Lynda; Rushton, Elizabeth; Atkinson, Lucy; Cornelissen, Eef; De Schrijver, Jelle; Stadnyk, Tetiana; Stubbs, Joshua; Su, Chrissy; Turkenburg-van Diepen, Maria; Veneu, Fernanda; Blake, Celena; Calvert, Saul; et al.
ABSTRACT: Large-scale intervention in the Earth's climate system is increasingly present in discussions about possible responses to climate change. Young people's perspectives have tended to be under-represented despite the intergenerational consequences of policy in this field. We report on a novel approach to research and practice: the co-creation of a youth guide and policy brief by youth participants and facilitators. The model offers potential use by practitioners for engaging publics at the early stages of technoscientific innovations. Findings fall into two categories: youth priorities for geoengineering and authorial responsibility as a way of supporting youth action. Tentative conclusions from youth participants are (i) action must be prioritised now to mitigate and adapt to climate change, rather than continuing with 'business as usual'; and (ii) there is a need for proactive international cooperation on governance and research on geoengineering to understand potential environmental and social consequences of geoengineering proposals for people at different temporal and spatial scales. Greater public dialogue on geoengineering and its governance is needed, particularly involving young people. The youth guide and policy brief co-authored by participants and facilitators, and the dialogic methods used in their production, can contribute to this dialogue.